The Female Reproductive Cycle of the Bedriaga Plate-Tailed Gecko, Teratoscincus bedriagai (Sauria: Gekkonidae) in Iran - Mojibi, Fatemeh; Hojati, Vida (International Journal of Zoology, 2014)
The Bedriaga Plate-tailed Gecko, Teratoscincus bedriagai Nikolsky, 1900, is distributed in the northern and eastern desert basins of the Central Plateau of Iran, Sistan, and the desert regions of southern Afghanistan. Iranian specimens are believed to be rare in collections. In this study, the reproductive cycle of this species has been investigated through focusing on oogenesis from 5 April to 5 August, 2013. Generally, 15 adult females were collected by hand at midnight from southern parts of Damghan County, situated in Semnan Province of Iran. Ovaries were removed and processed for the purpose of histological and morphometric studies. The results revealed that oocyte growth starts in early April and terminates in late July. Moreover, mating commences in spring, especially at the beginning of May, with oviposition occurring from late May to late July. Approximately, 1 to 2 eggs are laid by females per clutch with the possibility of producing a secondary clutch later in the season. The maximum reproductive activity takes place in May and continues with a decreasing trend in June and more reduction in July and finally ends in August. No significant difference was observed between right and left side of reproductive system. Therefore, oogenesis occurs from April to July, while T. bedriagai follows an oogenic cycle typical for temperate species.